Waqf based forest bio bank model - Yaakob, Adzidah; Imam Supaat, Dina; Zakaria, Mohamad Zaharuddin; Mustafa, Maizatun; Wook, Izawati; Mohamed Razali, Rodziana; Mahzir, Nurulnadiah (2018)
Product description The primary aim of Waqf Based Forest Bio Bank Model is to sustain forested area and its biodiversity in Malaysia using waqf principles i.e. perpetuity, irrevocability and inalienability. Forest and waqf stakeholders such as Forestry Department, Religious Council are involved in interview and round table discussion sessions in refining the proposed models (two models). This product is an innovative alternative mechanism of forest conservation that allows public participation in multiple forms. This product is expected to have potential impact towards ummah in terms of its contribution through several means i.e. cash waqf, waqf land, sukuk waqf. Hence, it offers fair distribution of wealth and benefits of healthy environment among public.